Study on heavy haul locomotive behaviour under a bogie traction control strategy with the presence of wheel diameter difference within a bogie - Spiryagin, M.; Wolfs, Peter; Cole, C.; Sun, Y.; Szanto, F. (2016)
© 2016 Taylor & Francis Group, London. Understanding the traction capabilities of real locomotives is a quite complex task because a great number of limitations and uncertainties are involved in the process. One of the design parameters that has a significant influence on tractive effort able to be achieved by a locomotive iswheel diameter. The variation of wheel diameters in a three-powered-axle bogie affects tractive effort and usually has its own predefined limits for operational practice. The experimental approach for determining its influence is not a practical one due to high costs relating of such studies. The numerical approach by means of the application of advanced simulation techniques is a very reasonable technique to develop the required knowledge in this field. This paper describes a methodology required for the study in order to describe a heavy haul locomotive’s behaviour in a continuous traction model under a bogie traction control strategy.